Miftah’s Communication Model and Da’wah Strategy in Narcotics Prison on The Gus Miftah Official YouTube Channel - Erwin; Wahyu Agung Prasongko; Luluk Fikri Zuhriyah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Da’wah is an activity aimed at inviting, calling, or guiding humanity to do good, so they obey Allah’s commands and avoid His prohibitions. An effective communication model and strategy are crucial for the preacher in delivering dakwah so that the message conveyed can be received, understood, and applied by the audience in their daily lives. The focus of this research is to examine the communication model and digital dakwah strategy on Gus Miftah’s YouTube channel through one of the videos titled “Gus Miftah Visits Prisoners in Prison.” This research uses a narrative qualitative approach. Narrative research is a study that explores the lives of individuals or groups as told or documented. Based on the results of the research and analysis, it was found that Gus Miftah, in delivering his dakwah or sermon in the Narcotics Prison, utilized several communication models: the informative communication model (providing information), the persuasive communication model (inviting, motivating, and influencing), the recreational communication model (delivering with humor), and the extemporaneous communication model (noting key points and delivering them flexibly). Additionally, Gus Miftah, in his sermon or dakwah video at the Narcotics Prison, used two dakwah strategies: the sentimental strategy (appealing to feelings, emotions, or the heart) and the rational strategy (through reason and intellect). Keywords: Communication, Da’wah, Startegy, Gus Miftah, Youtube